Naming the artist, composing the Philippines listening for the nation in the National Artist Award - Matherne, Neal D. (University of California, Riverside, 2014)
This work is a critical analysis of art, memory and prestige in the early twentieth- and late twenty-first-century Philippines. I am concerned with the creation of the Philippine nation by various acts of commemoration and recognition (awards, exhibits, and concerts) through which artists are valorized, immortalized and celebrated. I answer three broad questions: (1) how do patron-client and kinship systems determine the national recognition of artists in the post-colonial world? (2) how is music used in the nation-building project? and (3) how is national mythology created and contested through the commemoration of individual artists in the Philippines? I approach Philippine area studies through discussions of the past in ethnomusicology, borrowing theory from memory studies and methodology from historical anthropology while expanding both fields with a consideration of expressive culture. To describe this interaction between state and artist, I focus on the National Artist Award (NAA), the highest honor bestowed upon an artist by the Philippine government. I begin by recounting an aberration of the nominating process: the 2009 National Artist Award controversy. Then-President Gloria Macapagal Arroyo deleted a name from the prestigious NAA nominee list and added artists with suspiciously close ties to her administration. Then, I analyze the 2010 re-performance of National Artist for Music Jose Maceda's Ugnayan , a multi-spatial composition for 20 radio stations. This work was originally performed in 1974 with the explicit support of then-First Lady Imelda Marcos. Finally, I describe a 2012 exhibit featuring the materials of National Artist for Music Felipe De Leon Padilla Sr. I sort through clashing characterizations of De Leon of as a "crisis composer" who served the Philippines at times of foreign and domestic peril. Reading against the grain of these public acts of commemoration and recognition, I provide an account from the "ground up" and consider how the public construction of national artists renders the Philippines into a unified conceptual whole.